Energy Supply Chains in the Digital Age: A Review of Current Research and Trends - Agnieszka A. Tubis; Honorata Poturaj (Energies)
(1) Background: Digital transformation is critical in further developing the energy supply chain. The attainment of successive levels of digital maturity by chain participants translates into numerous benefits related to the efficiency, cost, and effectiveness of the energy flows implemented. However, the increasing degree of digitalisation and automation generates an increased risk of cyberattacks and other challenges related to the operation of the smart grid. This paper presents the results of a literature review describing the phenomenon of digital transformation in the energy supply chain. (2) Methods: The literature review was performed using two review methods. First, a systematic literature review was conducted using the PRISMA method. However, due to unsatisfactory results, this review was supplemented by a search supporting a narrative review. (3) Results: Analysing the identified publications made it possible to distinguish nine leading research trends related to digital transformation in the energy supply chain. These trends were characterised based on the described research results, and all articles were classified into the corresponding categories. (4) Conclusions: The presented results provide interesting material for further research related to building resilience in the energy supply chain and selected Industry 4.0 tools for assessing and managing risks associated with the operation of the energy sector.